Evaluation of performance validity using a Rey Auditory Verbal Learning Test forced-choice trial. Issue 4 (18th May 2016) - Ashendorf, Lee; Sugarman, Michael A.
Abstract: Objective : Forced-choice (FC) recognition memory is a common performance validity assessment methodology. This study introduces and evaluates the classification accuracy of a FC recognition trial for the Rey Auditory Verbal Learning Test (RAVLT).Method : The present sample of 122 military veterans (Mean age = 35.4, SD = 9.3) were all administered the RAVLT along with the FC procedure as part of a full neuropsychological protocol. Veterans were assigned to valid ( n  = 94) or invalid ( n  = 28) groups based on outcomes of performance validity measures.Results : The FC procedure was found to have strong sensitivity (67.9%) and specificity (92.6%) in predicting validity group status based on a cutoff score of ≤ 13. The FC trial outperformed RAVLT recognition hits (sensitivity = 46.4%, specificity = 91.5%) as a predictor of invalid performance.Conclusions : The RAVLT FC is demonstrated to be an effective measure of performance validity and is recommended for use as an adjunctive trial for the RAVLT.